2006
DOI: 10.1093/brain/awm028
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal folate metabolism in foetuses affected by neural tube defects

Abstract: Folic acid supplementation can prevent many cases of neural tube defects (NTDs), whereas suboptimal maternal folate status is a risk factor, suggesting that folate metabolism is a key determinant of susceptibility to NTDs. Despite extensive genetic analysis of folate cycle enzymes, and quantification of metabolites in maternal blood, neither the protective mechanism nor the relationship between maternal folate status and susceptibility are understood in most cases. In order to investigate potential abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…In the cytoplasm, SHMT1 regulates the partitioning of one-carbon units between thymidylate biosynthesis and homocysteine remethylation (24), whereas in the nucleus SHMT1 is a source of folate-activated one-carbon units for thymidylate synthesis (16). Consequently, de novo thymidylate biosynthesis is impaired in the nuclei of Shmt1 null mice (15), and decreased Shmt1 expression increases Sp mutant (10), as well as in NTD-affected human fetuses (29), this is the first direct evidence that disruption of folate-and SHMT1-dependent thymidylate biosynthesis underlies NTD pathogenesis. Impairments in de novo thymidylate biosynthesis may disrupt neural tube closure by reducing proliferative capacity or by increasing genomic instability via misincorporation of uracil into DNA (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoplasm, SHMT1 regulates the partitioning of one-carbon units between thymidylate biosynthesis and homocysteine remethylation (24), whereas in the nucleus SHMT1 is a source of folate-activated one-carbon units for thymidylate synthesis (16). Consequently, de novo thymidylate biosynthesis is impaired in the nuclei of Shmt1 null mice (15), and decreased Shmt1 expression increases Sp mutant (10), as well as in NTD-affected human fetuses (29), this is the first direct evidence that disruption of folate-and SHMT1-dependent thymidylate biosynthesis underlies NTD pathogenesis. Impairments in de novo thymidylate biosynthesis may disrupt neural tube closure by reducing proliferative capacity or by increasing genomic instability via misincorporation of uracil into DNA (30).…”
Section: Discussionmentioning
confidence: 99%
“…2). 55 Defective thymidylate biosynthesis has been implicated in NTDs in humans and mouse models, [61][62][63] suggesting that adequate supply of nucleotides for cellular proliferation is essential for closure of the neural tube. dietary imposition of choline deficiency has been found to alter DNA and histone methylation patterns in fetal mouse hippocampus.…”
Section: Are the Predicted Correlations Between Biomarkers Of One-carmentioning
confidence: 99%
“…The incorporation of thymidine into DNA is suppressed by exogenous dUMP, owing to activation of de novo synthesis of dTMP, provided that 5,10-methylene tetrahydrofolate, a folate cycle intermediate, is available as cosubstrate. A recent study also used this test to analyze cell lines derived from human NTD fetuses and revealed that a subset of cases exhibit an abnormality in folate metabolism, which is presumably genetically determined (Dunlevy et al, 2007).…”
Section: Interaction Of the Splotch Mutation With Environmental Factomentioning
confidence: 99%